Ultimate Italian : beginner-intermediate - Bancheri, Salvatore, 1954-; Lettieri, Michael; Bancheri, Salvatore, 1954- (New York : Living Language, 2004)
1. Language--Italian
"Previously published as Living Language Italian all the way."
Includes index.
Keywords: Italian language -- Textbooks for foreign speakers -- English